Is a 'culture of plus-size women' the independent effect of neighborhood disadvantage on female BMI? A cross-sectional study in two Chilean Municipalities. (July 2021) - Robinovich, Jossiana; Bosma, Hans; Borne, Bart van der; Ossa, Ximena; Muñoz, Sergio; Krumeich, Anja
Abstract: Research has shown that neighborhood disadvantage has an effect on BMI that is independent of individual disadvantage, much more pronounced in women than in men. The mechanisms that explain this gender-specific effect are not yet clear. Since women's body size dissatisfaction is closely linked to gender differences in BMI inequalities, the independent effect of neighborhood disadvantage on female BMI may relate to a local culture of acceptance of female large bodies, that could influence women's parameters for body size dissatisfaction. This study explored how the relation between female BMI, neighborhood income, individual income and education is influenced by body size dissatisfaction in a random sample of 882 women aged 20–60 that reside in two Chilean Municipalities. Data have a two level structure (women nested in 17 neighborhoods); it was collected by direct survey, height and weight were measured with portable instruments. Disadvantaged neighborhoods house mainly poor and low educated women, whereas the wealthier ones were inhabited mostly by affluent women with postsecondary education. The proportion of women without a husband/partner and with more than three children in disadvantaged neighborhoods was higher than better off areas. Multilevel linear regression showed that neighborhood disadvantage had an effect on female BMI that was independent of women's income and education, which was explained by body size dissatisfaction. The mean BMI for body size satisfaction among women in disadvantaged neighborhoods was 2 kg/m 2 higher than in affluent areas, which suggests that a 'culture of plus-size women' would emerge in urban clusters of poverty. The findings signal that neighborhood effects on BMI would relate to the socioeconomic polarization of urban areas, with marked concentrations of poverty and wealth, and might be explained by the psychosocial pathways associated to social disadvantage that act in addition to the effects of material conditions to influence people's health. Highlights: Neighborhood disadvantage affects female BMI, independently of personal disadvantage. Psychosocial pathways may explain the neighborhood-BMI association in women. Neighborhood effects on BMI would relate to the social polarization of urban areas. Neighborhood disadvantage may affect women's BMI by exposure to concentrated poverty.